Human milk oligosaccharides combine with Bifidobacterium longum to form the “golden shield” of the infant intestine: metabolic strategies, health effects, and mechanisms of action - Shuo Yang; Junwu Cai; Qian Su; Qiaohui Li; Xiangchen Meng (Gut Microbes)
Human milk oligosaccharides (HMOs) are the third most important nutrient in human milk and are the gold standard for infant nutrition. Due to the lack of an enzyme system capable of utilizing HMOs in the infant intestine, HMOs cannot be directly utilized. Instead, they function as natural prebiotics, participating in the establishment of the intestinal microbiota as a “bifidus factor.” A crucial colonizer of the early intestine is Bifidobacterium longum (B. longum), particularly its subspecies B. longum subsp. infantis, which is the most active consumer of HMOs. However, due to the structural diversity of HMOs and the specificity of B. longum strains, studies on their synergy are limited. An in-depth investigation into the mechanisms of HMO utilization by B. longum is essential for applying both as synbiotics to promote early intestinal development in infants. This review describes the colonization advantages of B. longum in the infant intestinal tract and its metabolic strategies for HMOs. It also summarizes recent studies on the effect and mechanism of B. longum and HMOs in infant intestinal development directly or indirectly through the action of metabolites. In conclusion, further structural analysis of HMOs and a deeper understanding of the interactions between B. longum and HMOs, as well as clinical trials, are necessary to lay the foundation for future practical applications as synbiotics.